2022
DOI: 10.20944/preprints202211.0489.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Agronomics, Genomics, Breeding and Intensive Cultivation of Ciherang Rice Variety

Abstract: Ciherang rice variety was released in year 2000 and become a superior variety in Indonesia. In a decade, due to the excellent agronomic characteristics and high productivity, Ciherang gradually replace the mega-variety IR-64 and widely cultivate in almost 40% rice production area in Indonesia. In addition to its high grain yield, short straw, early maturity, and high productive tiller number, it had superior grain quality, such as long and slender grain shape, clean yellow color, aromatic, and high milled rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…Meanwhile, salt-sensitive ones had high values for leaf rolling, Na/K ratio, H 2 O 2 , and MDA content. These results were supported by previous studies such as those of Peng et al [76], Zhang et al [77], Dwiningsih et al [78], and Bhowmik et al [9]. Many studies indicated that all of the growth stages in rice plants under salinity stress conditions showed different responses to salt [79].…”
Section: Discussionsupporting
confidence: 83%
“…Meanwhile, salt-sensitive ones had high values for leaf rolling, Na/K ratio, H 2 O 2 , and MDA content. These results were supported by previous studies such as those of Peng et al [76], Zhang et al [77], Dwiningsih et al [78], and Bhowmik et al [9]. Many studies indicated that all of the growth stages in rice plants under salinity stress conditions showed different responses to salt [79].…”
Section: Discussionsupporting
confidence: 83%
“…Meanwhile, salt-sensitive ones had high leaf rolling, Na/K ratio, H2O2, and MDA content. These results were supported by the previous studies such as Peng et al [91], Zhang et al [92], Dwiningsih et al, [93], and Bhowmik et al [10]. Many studies indicated that all of the growth stages in rice plants under salinity stress condition showed different responses to salt [94].…”
Section: Discussionsupporting
confidence: 81%
“…Fermentation process in the rice bran produced new compounds that were not identified in the non-fermented rice bran, such as nicotinic acid, isorhamnetin, isorhamnetin 7-glucoside, and quercetin. Fermented rice bran also produce aroma like vanilla, caramel, sweet, pungent, cereal, acid, rancid, smokey, nutty, fatty, milky, grass, and earthy [66,67]. The results showed that a total of 72 non-volatile compounds were investigated, including carbohydrates, nucleotides, peptides, vitamins, amino acids, lipids, and secondary metabolites.…”
Section: Rice Bran Of Cempo Irengmentioning
confidence: 99%